Reflection & Projection Women's "Special Treatment" in the 2024 Election Regulations: Study of PKPU 10/2023 - BUDHIATI, Ida; PRABOWO, Rian Adhivira (Journal of Political And Legal Sovereignty, 2023)
Purpose - During the 2024 election, the KPU issued PKPU 10/2023, which regulates candidacy. PKPU 10/2023 contains changes to a new method for calculating decimals for calculating women's quotas in electoral districts. The question arises: Does PKPU 10/2023 contain the spirit of special treatment in the interests of women? For this purpose, this study was carried out by departing from three aspects: (i) The historicity of the dynamics of "special treatment" in the 1945 Constitution.Methodology – Also considered in this section are the circumstances and conditions that served as the background for including special treatment provisions in the constitution, along with the dynamics surrounding them. (ii) Precedents in Constitutional Court Decisions which provide rules for the meaning of special treatment. (iii) The role of the KPU as a regulator in formulating its regulations, namely the attribution of authority possessed by the KPU to translate the spirit of the constitution towards special treatment. Finally, (iv) the substance of the PKPU 10/2023 norm itself is reviewed for conformity with the norms.Findings - In succession, the following were found: First, from a historical perspective, the special treatment of women's political quotas shows a tendency for constitutional interpretations to open space for women's political involvement. Second, the KPU as the regulator has a strategic role in interpreting the constitutional spirit, including special treatment for women. Third, regarding substance, the content of norms contained in PKPU 10/2023 is different from Law 7/2017 and the 1945 Constitution.Implication - From these three aspects, this study concludes that PKPU 10/2023 shows a discrepancy in the spirit of special treatment in capturing the interests of women's political representation. There should be changes to PKPU 10/2023 norms while maintaining the special treatment provisions for women as contained in PKPU 20/2018.